Healthcare-associated infection and antimicrobial use among residents of long-term care facilities in Italy: Preliminary results of a point prevalence survey - Lorenzo Brambilla; Lolita Azrumelashvili; Manfredi Grasso; Assunta Gabrielli; Donatella Lania; Andrea Labruto; Letizia Oreni; Roberto Pupillo; Maria Rosa Sbardellati Tommaso Petitti; Antonio Schirripa; Federica Tartarone; Luciana Bevilacqua (Journal of Infection and Public Health)
Background: Healthcare-associated infections (HAIs) are infections acquired in any care setting, including long-term residential facilities, rehabilitation units, and nursing homes, and which were not clinically manifest nor incubating at the time of admission to the facility. HAIs are among the most frequent adverse events encountered in healthcare settings, often caused by multi-resistant microorganisms that can infect patients, healthcare workers, and visitors, causing morbidity and mortality. Surveillance activities such as prevalence studies represent an opportunity to plan preventive actions and improve quality of care in all care contexts. Methods: A point prevalence survey was conducted in November 2023 among the 22 long-term care facilities (LTCFs) managed by the Don Carlo Gnocchi ONLUS Foundation. Data were collected on a single day in each LTCF, using a web-based data collection methodology developed for the European HALT-4 study. Data collection teams at each facility, including a total of 97 surveyors, completed a survey-questionnaire, following training on the data collection method. Results: Among the 2746 included residents, the prevalence of residents with at least one HAI was 4.8 % (95 % confidence interval [CI] 4.0 %–5.7 %). HAI prevalence ranged from 1.1 % (95 % CI 0.5 %–1.7 %) in residential care settings to 12.1 % (95 % CI 8.0 %–16.2 %) in intensive rehabilitation units. The prevalence of antimicrobial use was 7.3 % (95 % CI 6.3 %–8.3 %), with prevalence of 2.0 % (95 % CI 1.2 %–2.7 %) for residential care residents, 10.2 % (95 % CI 8.5 %–11.9 %) for non-intensive rehabilitation, and 20.2 % (95 % CI 15.2 %–25.2 %) for intensive rehabilitation. Conclusions: This initial study allowed the assessment of the feasibility of conducting nationwide studies in various centers, and deepened our understanding of different care settings, as well as the clinical characteristics and complexity of hospitalized patients and residents in LTCFs.